ANALYSIS OF THE ROLE OF DIGITAL LEADERSHIP AND TRANSFORMATIONAL LEADERSHIP ON THE PERFORMANCE OF KOREM 011-LILAWANGSA APPARATUS WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Ali imran; Herman Fithra; Marbawi; Jullimursyida; Mohd. Heikal; Sapna Biby (CV. Radja Publika, 2026)
This study aims to analyze the influence of digital leadership and transformational leadership on the performance of Korem 011-Lilawangsa apparatus with organizational commitment as an intervening variable on Korem 011-Lilawangsa apparatus, for the dependent variable of this study is digital leadership and transformational leadership for the independent variable is apparatus performance, for the intervening variable is organizational commitment.The population in this study was 350 Korem 011-Lilawangsa personnel. The sampling technique used simple random sampling and obtained a sample of 170 respondents who were Korem 011-Lilawangsa personnel. The research method used was a quantitative method, for the data analysis method using Structural Equation Modeling (SEM).The results of this study indicate that digital leadership has a significant effect on organizational commitment, transformational leadership has a significant effect on organizational commitment. Digital leadership has a significant effect on the performance of Korem 011-Lilawangsa apparatus, transformational leadership has a significant effect on the performance of Korem 011-Lilawangsa apparatus.